2018
DOI: 10.1017/jog.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimates of glacier change rates at Nevado Coropuna Ice Cap, Peru

Abstract: Accurate quantification of rates of glacier mass loss is critical for managing water resources and for assessing hazards at ice-clad volcanoes, especially in arid regions like southern Peru. In these regions, glacier and snow melt are crucial dry season water resources. In order to verify previously reported rates of ice area decline at Nevado Coropuna in Peru, which are anomalously rapid for tropical glaciers, we measured changes in ice cap area using 259 Landsat images acquired from 1980 to 2014. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 42 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…Bury et al (2013) [153] concluded that many catchments in the tropical Andes already passed their peak annual discharge and are now experiencing decreased volumes, which will impact future water availability security. In contrast, the Nevado Coropuna Ice Cap, presently the most extensive ice mass in the tropics, is shrinking considerably slower than previously studies argued, and it has been predicted that it will contribute to water supply until around 2120, which differs from previously predictions by almost 100 years [127].…”
Section: Water Resourcesmentioning
confidence: 57%
See 1 more Smart Citation
“…Bury et al (2013) [153] concluded that many catchments in the tropical Andes already passed their peak annual discharge and are now experiencing decreased volumes, which will impact future water availability security. In contrast, the Nevado Coropuna Ice Cap, presently the most extensive ice mass in the tropics, is shrinking considerably slower than previously studies argued, and it has been predicted that it will contribute to water supply until around 2120, which differs from previously predictions by almost 100 years [127].…”
Section: Water Resourcesmentioning
confidence: 57%
“…Predicting future glacial changes in the Peruvian Andes has proven challenging. For example, while Quelccaya Ice Cap could completely lose its accumulation zone before the end of the 21st century [125,126], some other extensive ice masses such as Nevado Coropuna in the Cordillera Ampato in southern Peru might not disappear completely until the 2120s [127].…”
Section: Tropical Andesmentioning
confidence: 99%
“…Both incorrect data (surface and date) have been used in many subsequent works about the Coropuna (e.g., Racoviteanu et al [64]), who due to the original mistake, calculated wrong values. Kochtitzky et al [65] have made the most recent and exhaustive work (259 Landsat images 1980-2014), obtaining results and conclusions very similar to Úbeda [51]. Moreover, Kochtitzky et al [65] have also pointed out previous works mistakes, which interpreted snow as glaciers.…”
Section: Glacier Surfacesmentioning
confidence: 88%
“…Kochtitzky et al [65] have made the most recent and exhaustive work (259 Landsat images 1980-2014), obtaining results and conclusions very similar to Úbeda [51]. Moreover, Kochtitzky et al [65] have also pointed out previous works mistakes, which interpreted snow as glaciers. Furthermore, they detected lower deglaciation rates and made the most recent measurement of the glacier surface (~44.1 ± 3.9 km 2 in 2014).…”
Section: Glacier Surfacesmentioning
confidence: 88%
“…20 These stratovolcanoes are covered by the most extensive glacial system in the tropics. 21,22 The glacier system surface area in 2010 was S 2010 =~46 km 2 ; the area's equilibrium line altitude (ELA) in the same year was ELA 2010 = 5,984 m, and the past ELA depression was much greater than at present, almost 1,000 m during the late Pleistocene. 22 Nearly all of the Coropuna lava flows are completely glaciated or cut by glacial valleys.…”
Section: Study Areamentioning
confidence: 99%